A study of the novel vision guided IV trajectory tracking control system based on expected yaw velocity. (May 2019) - Wang, Ruochen; Ye, Qing; Cai, Yingfeng; Xu, Xing; Meng, Xiangpeng; Long, Chen
Highlights: A new vision guided IV trajectory tracking control algorithm based on expected yaw velocity is proposed. A new virtual driving path between IV and preview point based on vehicle coordinate is proposed. The back-stepping sliding mode controller is adopted to promote the tracking accuracy and robustness of intelligent vehicle. The effectiveness of designed controller has been verified through the contrast simulations. Abstract: A novel vision guided intelligent vehicle (IV) trajectory tracking control algorithm based on expected yaw velocity is proposed to compensate for traditional vision guided trajectory tracking controller limitations in robustness and trajectory tracking accuracy. In this paper, the structure and mechanism of trajectory tracking controller based on expected yaw velocity is briefly introduced at first. The designed trajectory tracking controller models of IV system are then derived through the dynamic models and motion models of IV by using Matlab/Simulink. Simulations under two different road conditions and different preview distances are used to validate the superiority of designed trajectory tracking controller in comparison with traditional vision guided trajectory tracking controller. The effectiveness of designed trajectory tracking controller has been verified by simulation results, in which the robustness and trajectory tracking accuracy of designed trajectory tracking controller has been improved significantly. Finally, the novel controller is designed based on Simulink results, and test results reconfirm that the partial performances of controller effectively.